Powder Coating Waste Utilization as a Filler in High-Density Polyethylene (HDPE) Coupled with PP-g-MA - Shinta Dewi Ariantika; Mochamad Chalid; Azizah Intan Pangesty (Jurnal Sains Materi Indonesia, 2025)
The powder coating process in industry typically generates waste during curing process. This non-recyclable and hazardous powder-coating waste is utilized as filler material in this research. Polyester was employed as filler in the High-Density Polyethylene (HDPE) Matrix Composite. The study investigated the impact of polyester composition at 20%, 30%, and 40%, with 5% of PP-g-MA coupling agent addition. To assess the effect as a coupling agent, 0%, 2%, 5%, and 10% of PP-g-MA were added to the composite with a matrix-filler ratio of 70:30. Mixing was conducted using the hot melt mixing method at 180°C and mixing speed 60 rpm, with duration 9 minutes. The characterization and tests include the measurements of surface tension using SEM, FTIR, TGA, DSC, and micro-tensile tests. The results indicate that polyester and PP-g-MA composition decrease the thermal properties of the composite. However, increasing the filler addition by up to 30% and PP-g-MA addition by up to 5% enhances the thermal properties. The tensile strength and stiffness of the composite with polyester filler and PP-g-MA are higher than pure HDPE. These are achieved with the addition of polyester filler 20% and a coupling agent composition of PP-g-MA at 5%.